The role of smartphone-based weather information acquisition on climate change perception accuracy: Cross-country evidence from Kyrgyzstan, Mongolia and Uzbekistan - Begaiym Emileva; Lena Kuhn; Ihtiyor Bobojonov; Thomas Glauben (Climate Risk Management, 2023)
Individual perception about climate risks is critical for adopting mitigation and adaptation measures, yet international experience shows that individual perception might fundamentally deviate from objective changes. So far, little attention has been paid in the literature to understanding the role of ICTs in improving the accuracy of farmers' perceptions of actual drought occurrence. Therefore, this study aims to fill this gap by analyzing the discrepancy between farmers' subjective perceptions and actual drought occurrence. Furthermore, the study investigates the role of smartphone-based weather information on accurate perception of drought. Subjective drought assessment was obtained by a cross-sectional dataset of 2830 farm-level observations collected in Kyrgyzstan, Mongolia and Uzbekistan in 2021. For measuring objective meteorological drought occurrence, this study employs a standardized precipitation evapotranspiration index (SPEI) based on satellite imagery. The role of smartphone-based weather information acquisition on drought perception accuracy was measured by Propensity score matching. The comparison of objective and subjective assessment showed that 67 percent of farmers in Kyrgyzstan, 32 percent in Mongolia and 46 percent in Uzbekistan perceived meteorological drought inaccurately. The PSM estimates indicate that smartphone-based weather information acquisition significantly influences accurate meteorological drought perception. With these results, we advocate for higher attention to improving internet speed in rural areas and providing online weather information also to farmers with low digital literacy and low incomes.
Keywords: 330; drought risk perception; SPEI; weather information; Kyrgyzstan; Mongolia; Uzbekistan